Prolonged neutropenia due to antihuman neutrophil antigen 2 (CD177) antibody after bone marrow transplantation. Issue 7 (1st December 2016) - Wada, Taizo; Miyamoto, Satoshi; Okamoto, Hiroyuki; Matsuda, Yusuke; Toma, Tomoko; Imai, Kohsuke; Takagi, Masatoshi; Morio, Tomohiro; Yachie, Akihiro
Abstract: We describe a patient who presented with prolonged neutropenia due to anti‐human neutrophil antigen (HNA)‐2 (CD177) antibody after allogeneic bone marrow transplantation. A granulocyte immunofluorescence test showed bimodal expression of antineutrophil antibody that resulted from specific binding of anti‐HNA‐2 to CD177 + neutrophils from healthy donors. The patient did not respond to granulocyte colony stimulating factor, which is able to upregulate CD177 expression on neutrophils. The low percentage of CD177 + cells in the few remaining neutrophils supports the possibility of elimination of CD177‐upregulated neutrophils. These findings might explain an inferior response to neutrophil growth factors in neutropenia secondary to anti‐HNA‐2 antibody.